Effects of nitrogen fertilization on the abundance of enchytraeids and microarthropods in Scots pine forests - Lohm, Ulrik; Lundqvist, Heléne; Persson, Tryggve; Wirén, Anders (1977)
The effect on the abundance of enchytraeids and microarthropods of the nitrogen fertilizers, ammonium nitrate and urea, was studied. The experimental sites were three Scots pine stands in central and northern Sweden. Doses of fertilizers were similar to those used in practical forestry in Sweden but the effects of different doses of ammonium nitrate were also investigated. A significant decrease in the abundance of Enchytraeidae, Collembola and Cryptostigmata after ammonium nitrate fertilization was observed in one of the experiments. On the basis of this study and previous investigations, the following patterns of response to nitrogen fertilizers are discussed: 1) A shortterm effect with decreased abundance owing to ammonium toxicity or a "salt effect". 2) A long-term effect with increasing abundance resulting from increased food supply.